CO₂ adsorption on zeolites and Fe-MOF for carbon capture and storage (CCS) - Daud, Nor Khonisah; M. Najib, N. H. I. (Universiti Malaysia Pahang, 2022)
This research focused on the development of suitable materials for capturing and storing CO2 (CCS). Ferum-metal organic framework (Fe-MOF) and zeolite were prepared as adsorbents for the CO2 adsorption process. These adsorbents were characterised by employing X-ray diffraction (XRD) and Fourier Transform Infrared (FTIR) analysers. The adsorptive capacity of CO2 was conducted in an assembled facility containing of a metallic tubular container set up with a pure CO2 gas stream from a cylinder-shaped tank. The performance of these two adsorbents was investigated using two different parameters which are operating pressure and dosage of adsorbents. The exit concentration of CO2 was analyzed periodically using gas chromatography. Based on the FTIR and XRD studies, the findings suggest that the zeolite and Fe-MOF were successfully formed. The optimal adsorption conditions obtained for both adsorbents were 0.3 g of adsorbent dose and 1 bar of operating pressure. In conclusion, zeolite exhibits better performance as a CO2 adsorber due to its higher adsorption capacity than Fe-MOF.